Penegakan Hukum Pidana terhadap Penanganan Gelandangan dan Pengemis di Tempat Umum: (Studi Komparatif KUHP Lama dan Baru Berdasarkan Putusan PN Kab. Semarang No.145/Pid.C/PN UNR ) - Gunawan Widjaja; Songga Aurora Abadi; Alam Anbari (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The phenomenon of homelessness and begging in public places remains a complex social problem that impacts public order and legal norms. The main problem in this study is how criminal law is applied to homelessness and begging in public places, and how the provisions compare in the old Criminal Code and the new Criminal Code based on Law Number 1 of 2023. This study uses a normative juridical method with a legislative approach and literature study. In the old Criminal Code, begging is regulated in Article 504, which threatens imprisonment for anyone who begs in public. Meanwhile, the new Criminal Code regulates similar acts in Article 425, which no longer uses the term "begging" explicitly, but regulates the prohibition against the repeated exploitation of certain activities in public places that disturb the community. The results of the study show that although there is continuity in substance, the new Criminal Code tends to use a more humanistic approach and emphasizes social rehabilitation. Law enforcement against homelessness and begging still faces various obstacles such as low public reporting, limited police supervision, and a lack of rehabilitation facilities. Therefore, the main conclusion of this study is that a repressive approach alone is insufficiently effective. An integrated legal strategy is needed, combining penal and non-penal approaches with the active involvement of the government, the community, and social institutions.